POPULARITAS PERTUNJUKAN SENI ORGAN JAIPONG DI KABUPATEN SUMEDANG - Nalan, Arthur S; Afriyanto, Suhendi (Institut Seni Indonesia (ISI) Surakarta, 2020)
The Organ Jaipong is one of the popular arts that has developed in the Sumedang district. The existence of this art is quite new, but its popularity is well-known enough to attract enthusiasm from the public. This research focuses on factors have made of Organ Jaipong so popular, In analyzing this problem, the author applies the popular culture theory expressed by Raymond Williams as the main theory and uses Lawrence Grossberg's thinking as a supporting theory. This study uses a qualitative method with a descriptive analysis approach. The results of this study reveal that the origin of the Organ Jaipong developed and gained popularity was spearheaded by Edi Supriyadi, then re-developed by Dedi Budiman and Dani Maulana so that the Organ Jaipong was known to this day. The popularity of the Organ Jaipong is caused by several factors including: the sale of gamelan styles, the giving of the gamelan style, through oral, embedded in invitation papers, compact disc (CD) production, the role of the internet media, and the existence of urbanization.